2018
DOI: 10.19080/ctbeb.2018.16.555933
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents, Antibacterial and Antioxidant Activities of some Medicinal Plants

Abstract: The present study provides a detailed description of the phytochemical analysis, physiological features and biological activities of four selected plant species, namely Calligomum polygnoides subsp. comosum and Nicotiana glauca collected from the coastal desert in the Delatic Mediterranean Sea, as well as Hyoscyamus muticus and pulicaria undulate subsp. Undulata collected from the inland desert in Wadi Hagul and Wadi El-Molaak in the North of Eastern Desert in Egypt. The obtained results showed that, the studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
3
5
1
Order By: Relevance
“…On the other hand, root and stem extracts had no inhibition activity against both bacteria, similar to our findings (Alghamdi, 2021). Aldesuquy et al, (2018) indicated that the aqueous shoot extract of N. glauca showed antimicrobial activity against B. subtilis (14.50±0.50 mm), Klebsiella pneumonia (13.00±0.66 mm), Streptococcus pyogenes (11.00±0.12 mm), Candida albicans (11.00±0.35 mm), Erwinia carotovora (8.50±0.50 mm) and E. coli (7.50±0.36 mm), respectively. But, the extract was no inhibitory effect against S. aureus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, root and stem extracts had no inhibition activity against both bacteria, similar to our findings (Alghamdi, 2021). Aldesuquy et al, (2018) indicated that the aqueous shoot extract of N. glauca showed antimicrobial activity against B. subtilis (14.50±0.50 mm), Klebsiella pneumonia (13.00±0.66 mm), Streptococcus pyogenes (11.00±0.12 mm), Candida albicans (11.00±0.35 mm), Erwinia carotovora (8.50±0.50 mm) and E. coli (7.50±0.36 mm), respectively. But, the extract was no inhibitory effect against S. aureus.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the use of different plant parts such as shoot, they found that the aqueous extract was efficient against E. coli, which is contrary to our findings. However, like in our study, they also revealed that the extract was ineffective against S. aureus (Aldesuquy et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Earlier conducted research indicated maximum antibacterial activity of C. polygonoides ethanolic extract stem against E. Coli 9.40 mm and S. Aureus 14.60 mm ( Mukhtar et al, 2018 ). While shoot extract of it exhibited no activity against E. Coli and 11.00 ± 0.90 mm inhibition zone against Staphylococcus aureus ( Heshmat et al, 2018 ). It was also found in case of another member of Polygonaceae family, Calligonum arich L. where the plant’s methanol extract demonstrated high inhibition activity 15.00 ± 0.20 mm and 10.80 ± 0.16 against S. aureus and , respectively ( Yahia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential association of anabasine with bees' mortality should be treated with caution, considering that the administered plant extracts may contain other plant toxins, not included in the analytical method. Nevertheless, studies on N. glauca content have demonstrated several constituents such as sesquiterpenes, diterpenoids, and phenols in addition to alkaloids [45,46]. In this context, such compounds although prevalent, are not expected to provoke substantial effects on bees, not omitting of course the combined effects that are to a large extent underexplored.…”
Section: Discussionmentioning
confidence: 99%